A cross-cultural comparison of organisational commitment amongst vehicle sales staff - C. F. Magano; A. Thomas; G. P. De Bruin (South African Journal of Business Management, 2011)
The automotive industry is regarded as being critical to the economic growth of South Africa (Horn, 2007). As the achievement of organisational goals occurs largely through the performance of committed human resources (Nijhof, De Jong Beukhof, 1998), the purpose of the present study was to gain a deeper understanding of the differences in organisational commitment amongst different language groups (language being a proxy of culture) of vehicle sales staff at a large South African motor retailer.The unit of analysis for the study was individual employees (n=314) and the data were collected through the administration of the TCM survey questionnaire developed by Allen and Meyer (1990) to measure affective, normative and continuance commitment. The majority of respondents (36,90%) were African language speakers, 32,30% were English language speakers and 3,60% were Afrikaans language speakers.Results indicate that African language respondents scored significantly lower on normative commitment than did either the Afrikaans or English respondents. No significant differences in normative commitment were observed between the Afrikaans and English respondents.Given the strategic importance of the automotive industry to the South African economy, this finding could alert managers to the necessity of understanding the reasons for the lower normative commitment of the African language group (compared to the Afrikaans and English speakers) and, accordingly, to devise ways of increasing normative commitment with this group.
Keywords: 650